MEDSEA-FIN: An estimated DSGE model with housing and financial frictions for Malta - William Gatt (Central Bank of Malta, 2022)
This paper uses Bayesian techniques and Maltese data over the period 2001-2019 to estimate the parameters of MEDSEA-FIN, one of the Central Bank of Malta's DSGE models. The model captures linkages between the housing sector, banks and the rest of the economy via a borrowing collateral constraint. The paper shows that the data is informative on a subset of the parameters, and documents that the dynamic properties of the estimated model are in line with similar DSGE models estimated for other countries. The results corroborate recent empirical findings for Malta documented in other studies. The model is used to decompose recent macroeconomic data and shows that housing demand shocks were important drivers of house prices and credit. Shocks from the euro area also drove a significant share of macroeconomic fluctuations. The paper also shows that the model survives external validation tests. Although the model remains somewhat stylized along some dimensions, estimation makes it suitable for policy analysis related to housing and credit markets and associated macroprudential policies.
Keywords: C11; C32; C51; E21; E32; 330; MEDSEA-FIN; Bayesian estimation; house prices; structural shocks